Multi-grading composite fly ash and preparation method and application thereof
Through the technical means of multi -level compound coal ash, the problem of high water and insufficient strength activity of the existing modified flour ash materials is solved, and the effect of reducing the amount of water demand, increasing the intensity activity index, and improving concrete work performance.
Patent Information
- Application Number
- CN202411261882.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
AI Technical Summary
The existing modified fly ash materials require high water volume and further enhancement of strength and activity. The role of glass micro-beaded fly ash on concrete working performance has not been studied.
The multi -level compound coal ash is adopted, and the gradient mix is compounded by selecting different fine -grained ash ash and modified flour ash to form a gradient to retain the glass of glass, reduce the amount of water demand, and increase the intensity activity index.
A significant improvement of the quality of the product of the flour ash, avoiding the fluctuation of the abrasive quality, the problem of improving concrete water water and poor and poor prone, and improving the working performance and compressive strength of concrete.
Smart Images

Figure BDA0005035942340000121 
Figure BDA0005035942340000131 
Figure BDA0005035942340000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a multi-graded composite fly ash and a preparation method and application thereof. Background Art
[0002] Fly ash refers to the byproduct produced by burning coal in the process of thermal power generation. It contains rich active ingredients such as silicon dioxide, iron oxide, aluminum oxide, calcium oxide, and has morphological effect, activity effect and micro-aggregate effect (commonly known as the "three major effects"). When applied to concrete, it can not only replace part of the cement, but also improve the working performance and durability of concrete. Therefore, it is widely used in cement concrete and other projects. In some places, there is even a situation of supply exceeding demand. The annual output of fly ash in my country is about 600 million tons, and the utilization rate is about 70%. Some fly ash cannot be used due to reasons such as too coarse particles and low activity. Therefore, improving the existing fly ash and improving its utilization rate is an important way to improve the comprehensive utilization rate of fly ash.
[0003] Fly ash can improve the working performance and mechanical properties of concrete, mainly due to the glass beads present in fly ash. Current research shows that concrete prepared with fly ash mixed with glass beads has the characteristics of high working performance and low viscosity, and has good application prospects for the preparation of high-performance concrete and foamed concrete. Utilizing the filling effect of fly ash glass beads, it can be used as a cement admixture, which can not only fill the pores in the concrete, increase the density of the concrete, and thus improve the strength of the concrete, but also reduce the amount of cement, reduce environmental pollution, and improve economic benefits. At the same time, the glass beads are spherical and have a smooth surface, which can reduce the friction resistance in the concrete, make the concrete easier to flow, and thus improve the uniformity of the concrete.
[0004] The fly ash commonly used in the market is affected by the quality of coal used in thermal power plants. The fineness of the fly ash produced varies. The fineness of the original ash is generally greater than 30%, which does not meet the requirements of the national standard for the fineness of secondary fly ash. Therefore, manufacturers often use grinding to reduce the fineness of fly ash. During the grinding process, the original glass beads of fly ash are destroyed due to the extrusion of external forces, resulting in a decrease in the contribution to the fluidity of concrete at the application end, an increase in water demand, and a decrease in added value. At the same time, the ground ash produced by waste materials such as slag on the market also has the disadvantage of no glass beads.
[0005] Chinese patent CN116003012A "A physically modified fly ash and its preparation method" discloses a method of modifying fly ash by physical methods, limiting the particle size of fly ash, keeping glass beads intact to the maximum extent, reducing the water demand ratio of fly ash, and improving the strength activity index. However, its water demand is relatively high, and the strength activity still needs to be further improved, and the effect of glass bead fly ash on the working performance of concrete has not been studied.
[0006] Therefore, it is of great significance to provide a high-quality fly ash and its preparation method and application that can meet the fineness requirements, retain glass beads well, and improve the working performance of concrete. Summary of the invention
[0007] In view of the fact that the existing modified fly ash materials have a relatively high water demand, the strength activity still needs to be further improved, and the effect of glass bead fly ash on the working performance of concrete has not been studied, the present invention provides a multi-graded composite fly ash and a preparation method and application thereof. The multi-graded composite fly ash can significantly improve the product quality of fly ash, avoid quality fluctuations of ground ash, and at the same time can adjust and improve the problems of concrete flooding and poor workability caused by fly ash, thereby improving the working performance of concrete.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A multi-graded composite fly ash, comprising the following components by weight: 5-35 parts of original fly ash A, 15-35 parts of original fly ash B, and 35-55 parts of modified fly ash;
[0010] The fineness of the raw ash A is 40-60%;
[0011] The fineness of the raw ash B is 30-40%;
[0012] The fineness of the modified fly ash is 15-25%.
[0013] Furthermore, the modified fly ash is prepared by the following method:
[0014] The raw ash C and the modification aid are mixed and ground for 5-30 minutes to obtain the modified fly ash.
[0015] Furthermore, the fineness of the raw ash C is 30-40%.
[0016] Furthermore, the modification aid is triethanolamine, monoethanoldiisopropanolamine, glycerol and water, and the mass ratio is triethanolamine:monoethanoldiisopropanolamine:glycerol:water=(1-3):(1-3):(1-3):(4-6).
[0017] Furthermore, the fineness of the multi-graded composite fly ash is 20-30%.
[0018] Furthermore, the number of glass microbeads in the multi-graded composite fly ash within a circular field of view with a radius of 0.5 mm is ≥55.
[0019] Furthermore, the raw ashes A, B and C are Class F fly ash.
[0020] Another object of the present invention is to provide a method for preparing multi-graded composite fly ash.
[0021] A method for preparing multi-graded composite fly ash according to any one of the above items, characterized in that it comprises the following steps:
[0022] The original ash A, original ash B and modified fly ash are weighed and mixed according to the required proportion, and stirred to obtain the multi-graded composite fly ash.
[0023] Furthermore, the stirring time is 10-15 min.
[0024] Another object of the present invention is to provide an application of multi-graded composite fly ash.
[0025] An application of the above-mentioned multi-graded composite fly ash in cement concrete.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] The present invention provides a multi-graded composite fly ash. By selecting fly ash raw ash and modified fly ash of different finenesses for compounding to form a gradient combination, the glass microbeads in the fly ash can be better retained, which is beneficial to reducing the water demand ratio of the fly ash, improving the strength activity index, reducing the friction resistance in the concrete to ensure the fluidity of the concrete, and filling the pores in the concrete to improve the compactness of the concrete, and further improving the compressive strength of the concrete. The multi-graded composite fly ash can significantly improve the product quality of the fly ash, avoid the quality fluctuation of the ground ash, and at the same time can adjust and improve the problems of concrete flooding and poor workability caused by the fly ash, thereby improving the working performance of the concrete.
[0028] The modified fly ash of the present invention can accelerate the hydration reaction in the concrete system and thus improve the early strength of the concrete by adding triethanolamine to improve the grinding efficiency; continuously promote the late hydration reaction of fly ash by adding monoethanol diisopropanolamine, and significantly improve the late strength of fly ash; by adding glycerol containing both hydrophilic hydroxyl groups and hydrophobic structures, it has solubilization and dispersion effects, and can improve the problems of concrete flooding and poor workability caused by fly ash. At the same time, the introduction of the modified auxiliary agent can improve the grinding efficiency and reduce the production energy consumption on the one hand, and accelerate the hydration reaction in the concrete system and improve the compressive strength of concrete at all ages on the other hand.
[0029] The invention provides a preparation method of multi-graded composite fly ash, which is simple and easy to operate, can significantly reduce production costs, is suitable for large-scale promotion and industrial production, shows significant environmental benefits and economic value, and has positive significance for promoting the sustainable development of the construction industry. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0031] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0032] The following examples are all cement pastes.
[0033] Example 1
[0034] A method for preparing multi-graded composite fly ash comprises the following steps:
[0035] S1. Preparation of a modification agent: Add 100g of triethanolamine, 300g of monoethanol diisopropanolamine, 100g of glycerol and 500g of water in a beaker and stir to obtain a modification agent;
[0036] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 60%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 22% of the modified fly ash;
[0037] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 1kg of Class F fly ash A (fineness of 50%), 3kg of Class F fly ash B (fineness of 30%), and 6kg of modified fly ash obtained in S2, mix, and stir for 10 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0038] Example 2
[0039] A method for preparing multi-graded composite fly ash comprises the following steps:
[0040] S1. Preparation of a modification agent: Add 300g of triethanolamine, 100g of monoethanol diisopropanolamine, 100g of glycerol and 500g of water into a beaker and stir to obtain a modification agent;
[0041] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 50%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 18% of the modified fly ash;
[0042] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 3kg of Class F fly ash A (fineness of 40%), 3kg of Class F fly ash B (fineness of 30%), and 4kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0043] Example 3
[0044] A method for preparing multi-graded composite fly ash comprises the following steps:
[0045] S1. Preparation of a modification agent: Add 100 g of triethanolamine, 300 g of monoethanol diisopropanolamine, 150 g of glycerol and 450 g of water into a beaker and stir to obtain a modification agent;
[0046] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 40%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 21% of the modified fly ash;
[0047] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 2.5kg of Class F fly ash A (fineness of 40%), 2kg of Class F fly ash B (fineness of 35%), and 5.5kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0048] Example 4
[0049] A method for preparing multi-graded composite fly ash comprises the following steps:
[0050] S1. Preparation of a modification agent: Add 300g of triethanolamine, 200g of monoethanol diisopropanolamine, 100g of glycerol and 400g of water in a beaker and stir to obtain a modification agent;
[0051] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 30%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 15% of the modified fly ash;
[0052] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 3kg of Class F fly ash A (fineness of 40%), 3kg of Class F fly ash B (fineness of 30%), and 4kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0053] Example 5
[0054] A method for preparing multi-graded composite fly ash comprises the following steps:
[0055] S1. Preparation of a modification agent: Add 200g of triethanolamine, 100g of monoethanol diisopropanolamine, 300g of glycerol and 400g of water in a beaker and stir to obtain a modification agent;
[0056] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 60%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 21% of the modified fly ash;
[0057] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 1kg of Class F fly ash A (fineness of 40%), 3kg of Class F fly ash B (fineness of 30%), and 6kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0058] Example 6
[0059] A method for preparing multi-graded composite fly ash comprises the following steps:
[0060] S1. Preparation of a modification agent: Add 200g of triethanolamine, 200g of monoethanol diisopropanolamine, 200g of glycerol and 400g of water in a beaker and stir to obtain a modification agent;
[0061] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness of 50%), spray 30gS1 obtained modified additive, mix thoroughly, and grind for 20min using a ball mill to obtain a modified fly ash fineness of 20%;
[0062] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 2kg of Class F fly ash A (fineness of 45%), 2.5kg of Class F fly ash B (fineness of 35%), and 5.5kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0063] Comparative Example 1
[0064] A method for preparing multi-graded composite fly ash comprises the following steps:
[0065] S1. Preparation of fly ash: Weigh 10kg of Class F fly ash C (fineness 60%), spray 30g of water, mix thoroughly, and grind using a ball mill for 20min to obtain a fly ash fineness of 46%;
[0066] S3. Preparation of multi-graded composite fly ash: In a mixing machine, 2kg of Class F fly ash A (fineness of 45%), 2.5kg of Class F fly ash B (fineness of 35%), and 5.5kg of fly ash obtained in S1 were added in sequence, mixed, and stirred for 12 minutes. After mixing evenly, the multi-graded composite fly ash was obtained.
[0067] Compared with Example 6, the main difference of this comparative example is that treated fly ash is used instead of modified fly ash, and its fineness is 46%.
[0068] Comparative Example 2
[0069] A method for preparing multi-graded composite fly ash comprises the following steps:
[0070] S1. Preparation of a modification agent: Add 200g of monoethanol diisopropanolamine, 200g of glycerol and 600g of water in a beaker and stir to obtain a modification agent;
[0071] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 50%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 32% of the modified fly ash;
[0072] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 2kg of Class F fly ash A (fineness of 45%), 2.5kg of Class F fly ash B (fineness of 35%), and 5.5kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0073] Compared with Example 6, the main difference of this comparative example is that treated fly ash is used instead of modified fly ash, and its fineness is 32%.
[0074] Comparative Example 3
[0075] A method for preparing multi-graded composite fly ash comprises the following steps:
[0076] S1. Preparation of a modifying agent: Add 200g of triethanolamine, 200g of glycerol and 600g of water into a beaker and stir to obtain a modifying agent;
[0077] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness 50%), spray 30gS1 obtained modified additive, mix thoroughly, use a ball mill to grind for 20min to obtain a fineness of 28% of the modified fly ash;
[0078] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 2kg of Class F fly ash A (fineness of 45%), 2.5kg of Class F fly ash B (fineness of 35%), and 5.5kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0079] Compared with Example 6, the main difference of this comparative example is that treated fly ash is used instead of modified fly ash, and its fineness is 28%.
[0080] Comparative Example 4
[0081] A method for preparing fly ash comprises the following steps:
[0082] In a mixing machine, add 10 kg of Class F fly ash A (fineness of 45%) and stir for 12 minutes to obtain the fly ash.
[0083] Compared with Example 6, the main difference of this comparative example is that it only contains raw ash A, and its fineness is 45%.
[0084] Comparative Example 5
[0085] A method for preparing fly ash comprises the following steps:
[0086] In a mixing machine, add 10 kg of Class F fly ash B (fineness of 35%) and stir for 12 minutes to obtain the fly ash.
[0087] Compared with Example 6, the main difference of this comparative example is that it only contains raw ash B, and its fineness is 35%.
[0088] Comparative Example 6
[0089] A method for preparing fly ash comprises the following steps:
[0090] S1. Preparation of a modification agent: Add 200g of triethanolamine, 200g of monoethanol diisopropanolamine, 200g of glycerol and 400g of water in a beaker and stir to obtain a modification agent;
[0091] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness of 50%), spray 30gS1 obtained modified additive, mix thoroughly, and grind for 20min using a ball mill to obtain a modified fly ash fineness of 20%;
[0092] S3. Preparation of fly ash: In a mixing machine, add 10 kg of the modified fly ash obtained in S2 and stir for 12 minutes to obtain the fly ash.
[0093] Compared with Example 6, the main difference of this comparative example is that it only contains raw ash C, and its fineness is 20%.
[0094] Comparative Example 7
[0095] A method for preparing multi-graded composite fly ash comprises the following steps:
[0096] In a mixing machine, 2 kg of F-type fly ash A (fineness of 45%), 2.5 kg of F-type fly ash B (fineness of 35%), and 5.5 kg of ball-milled fly ash C (fineness of 20%) are added in sequence, mixed, and stirred for 41 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0097] Compared with Example 6, the main difference of this comparative example is that the raw ash C after ball milling is used to replace the modified fly ash, and its fineness is 20%.
[0098] Comparative Example 8
[0099] A method for preparing multi-graded composite fly ash comprises the following steps:
[0100] S1. Preparation of a modification agent: Add 200g of triethanolamine, 200g of monoethanol diisopropanolamine, 200g of glycerol and 400g of water in a beaker and stir to obtain a modification agent;
[0101] S2. Preparation of modified fly ash: Weigh 10kg of Class F fly ash C (fineness of 50%), spray 30gS1 obtained modified additive, mix thoroughly, and grind for 20min using a ball mill to obtain a modified fly ash fineness of 20%;
[0102] S3. Preparation of multi-graded composite fly ash: In a mixing machine, add 4kg of Class F fly ash A (fineness of 45%), 4kg of Class F fly ash B (fineness of 35%), and 2kg of modified fly ash obtained in S2, mix, and stir for 12 minutes. After mixing evenly, the multi-graded composite fly ash is obtained.
[0103] Compared with Example 6, the main difference of this comparative example is that the proportions of raw ash A, raw ash B and modified fly ash exceed the range.
[0104] The above embodiments and comparative examples were subjected to performance tests, and the experimental test methods were as follows:
[0105] The statistical method for the number of glass beads is as follows: take about 1g of fly ash sample that has been sieved through a 45μm square hole sieve, disperse the sample on a glass slide and let it stand for about 30s to ensure that the sample is fully dispersed and that the observation area is full of the sample. Use particle image analysis technology to identify and count the glass beads in a circular field of view with a radius of 0.5mm (magnification of 150 times). The number of glass beads is abbreviated as N. gb .
[0106] The determination method of fineness and water requirement ratio refers to GB / T 1596-2017 "Fly ash used in cement and concrete". The water requirement ratio refers to the ratio of the amount of water required to replace 30% of silicate cement with fly ash to the water requirement of silicate cement standard mortar under the specified cement standard mortar fluidity test method. The smaller the water requirement ratio, the better the quality of the fly ash, which can significantly reduce the mixing water consumption of concrete and improve the quality of concrete.
[0107] The determination method of strength activity index is shown in GB / T 1596-2017 "Fly ash used in cement and concrete". The strength activity index refers to the strength development ratio of the cementitious material prepared by mixing fly ash and standard silicate cement to the cementitious material prepared by mixing pure silicate cement. The higher the strength activity index of fly ash in concrete, the better its long-term strength development.
[0108] The C30 concrete required for this experimental example was prepared according to the conventional method, and the fly ash prepared in the embodiment and the comparative example was added respectively, and the raw materials and the proportion were m (cement): m (mineral powder): m (fly ash): m (sand): m (stone): m (water): m (admixture) = 177: 93: 80: 790: 1050: 165: 9.1. The admixture was a commercially available water-reducing polycarboxylate water-reducing agent, and the water-reducing rate was 27%.
[0109] The test method for concrete slump and expansion refers to GB / T 50080-2016 "Test method for performance of ordinary concrete mixtures".
[0110] Slump refers to the height of concrete slump in a cone mold, and spread refers to the degree of diffusion of concrete around the bottom of the cone mold during the slump test. The slump and spread of concrete are important indicators for measuring the workability of concrete, and have an important impact on the construction and performance of concrete. If the slump is too small, it means that the concrete is too dry and has poor fluidity; if the slump is too large, it means that the concrete contains too much water and has low strength. The greater the spread, the better the plasticity of the concrete and the stronger its molding ability, but too high a spread will cause shrinkage cracks in the concrete or lose stability.
[0111] A large number of tests have shown that the closer the ratio of the slump to the expansion of the concrete mixture is to 0.4, the better the workability of the concrete.
[0112] The test method of water bleeding rate refers to GB / T 50080-2016 "Test method for performance of ordinary concrete mixture". Water bleeding rate refers to the ratio of water bleeding amount to water content of concrete mixture. The smaller the water bleeding rate, the better the water retention performance of concrete.
[0113] The result is as follows:
[0114] Table 1 Properties and strength activity index of multi-graded composite fly ash prepared in Examples and Comparative Examples
[0115]
[0116] As can be seen from Table 1, the number of glass beads in a circular field with a radius of 0.5 mm in the multi-graded composite fly ash prepared in Examples 1-6 of the present invention is greater than 55, the water requirement ratio is lower than 95.0%, and the 28d strength activity index is above 84%, indicating that the multi-graded composite fly ash prepared by the technical solution of the present invention better retains the glass beads in the fly ash, the fly ash has a low water requirement ratio, and a high strength activity index.
[0117] In Comparative Examples 1-3, the fineness of the fly ash after treatment exceeded the range, and the 28d strength activity index was lower than 80%, indicating poor fly ash quality; in Comparative Examples 4 and 5, only one type of raw ash was used respectively, and the number of glass beads was high. Although the water demand was relatively low, the 28d strength activity index was greatly reduced compared with the embodiments; in Comparative Example 6, only modified fly ash was used, and the number of glass beads was only 24, and the 28d strength activity index was 88.3%, which was higher than that of the comparative examples, but its water demand ratio was as high as 101.1%; and in Comparative Example 7, raw ash C treated with ball milling was used to replace modified fly ash. Although the fineness met the requirements of national standards, the original glass beads were greatly destroyed due to long-term grinding, resulting in a water demand ratio of 100.7%, which was higher than that of the embodiments, and a low 28d strength activity index; in Comparative Example 8, the ratio of raw ash to modified fly ash was inappropriate, resulting in a fineness of 36.0%, which did not meet the requirements of GB / T 1596-2017 "Fly ash for cement and concrete", and the amount of modified fly ash is too little, resulting in a low 28d strength activity index of the final product.
[0118] Table 2 Performance of multi-graded composite fly ash concrete obtained in the examples and comparative examples
[0119]
[0120]
[0121] As shown in Table 2 and Table 1, the cement concrete using the multi-graded composite fly ash prepared in Examples 1-6 of the present invention has a slump and expansion within an appropriate range, good workability, a water seepage rate of no more than 2.0%, good water retention, and a 7-day compressive strength of more than 25 MPa, a 28-day compressive strength of more than 36 MPa, and a high compressive strength at each age.
[0122] In Comparative Examples 1-3, the fineness of the fly ash after treatment exceeded the range, and the 7-day compressive strength was lower than 25MPa, and the 28-day compressive strength was lower than 35MPa, and the compressive strength was low; in Comparative Examples 4 and 5, only one type of raw ash was used respectively, and the water bleeding rate was high, and the concrete water retention performance was poor; in Comparative Example 6, only modified fly ash was used, the slump was low, the concrete was too dry, the fluidity was poor, and the expansion was low. At the same time, the ratio of the two was 0.356, and the workability was poor compared with the embodiments; and in Comparative Example 7, raw ash C after ball milling was used to replace modified fly ash, and the concrete had low slump and expansion, and the workability was poorer than that of the embodiments, and the 7d and 28d concrete strengths were lower than those of the embodiments; in Comparative Example 8, although the slump and expansion of the concrete were within the normal range, due to the unreasonable proportion of raw ash and modified fly ash, the proportion of modified fly ash was low, resulting in a high water bleeding rate of the concrete, and the 7d and 28d compressive strengths were lower than those of Embodiments 1-6.
[0123] In summary, by selecting fly ash of different fineness and modified fly ash for compounding to form a gradient combination to obtain a multi-graded composite fly ash, the glass beads in the fly ash can be better retained, which is beneficial to reducing the water demand ratio of fly ash, improving the strength activity index, ensuring the fluidity of concrete, improving the compactness of concrete, and further improving the compressive strength of concrete. The multi-graded composite fly ash can significantly improve the product quality of fly ash, avoid the quality fluctuation of ground ash, and at the same time can adjust and improve the problems of concrete flooding and poor workability caused by fly ash. On the other hand, it can accelerate the hydration reaction in the concrete system, improve the compressive strength of concrete at all ages, and thus improve the working performance of concrete. The preparation method of the multi-graded composite fly ash is simple and easy to operate, can significantly reduce production costs, is suitable for large-scale promotion and industrial production, shows significant environmental benefits and economic value, and has positive significance for promoting the sustainable development of the construction industry.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A multi-graded composite fly ash, characterized in that: In terms of weight fraction, it includes the following components: 5-35 parts of raw ash A, 15-35 parts of raw ash B, 35-55 parts of modified fly ash; The fineness of the raw ash A is 40-60%; The fineness of the raw ash B is 30-40%; The fineness of the modified fly ash is 15-25%.
2. A multi-graded composite fly ash according to claim 1, characterized in that: The modified fly ash is prepared by the following method: The raw ash C and the modification aid are mixed and ground for 5-30 minutes to obtain the modified fly ash.
3. A multi-graded composite fly ash according to claim 2, characterized in that: The fineness of the raw ash C is 30-60%.
4. A multi-graded composite fly ash according to claim 2, characterized in that: The modification aids are triethanolamine, monoethanoldiisopropanolamine, glycerol and water, and the mass ratio is triethanolamine:monoethanoldiisopropanolamine:glycerol:water=(1-3):(1-3):(1-3):(4-6).
5. A multi-graded composite fly ash according to claim 1, characterized in that: The fineness of the multi-graded composite fly ash is 20-30%.
6. A multi-graded composite fly ash according to claim 1, characterized in that: The number of glass microbeads in the circular field of view with a radius of 0.5 mm of the multi-graded composite fly ash is ≥55.
7. A multi-graded composite fly ash according to claim 1, characterized in that: The raw ashes A, B and C are F-type fly ashes.
8. A method for preparing multi-graded composite fly ash according to any one of the preceding claims, characterized in that: The following steps are involved: The original ash A, original ash B and modified fly ash are weighed and mixed according to the required proportion, and stirred to obtain the multi-graded composite fly ash.
9. A method for preparing multi-graded composite fly ash according to claim 8, characterized in that: The stirring time is 10-15 min.
10. Use of the multi-graded composite fly ash according to any one of claims 1 to 9 in cement concrete.
Citation Information
Patent Citations
Physical modified fly ash and preparation method thereof
CN116003012A